2017
DOI: 10.3892/mmr.2017.6664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryopreservation on excretory function, cellular adhesion molecules and vessel lumen formation in human umbilical vein endothelial cells

Abstract: Cryopreservation is widely used in regenerative medicine for tissue preservation. In the present study, the effects of cryopreservation on excretory function, cellular adhesion molecules and vessel lumen formation in human umbilical vein endothelial cells (HUVECs) were investigated. After 0, 4, 8, 12 or 24 weeks of cryopreservation in liquid nitrogen, the HUVECs were thawed. The excretory functions markers (endothelin-1, prostaglandin E1, von Willebrand factor and nitric oxide) of HUVECs were measured by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that cryopreservation decreases the expression of certain adhesion molecules on CD34 + hematopoietic progenitor cells 6 . Human umbilical vein endothelial cells have also been shown to be vulnerable to cryopreservation which can lead to lowered angiogenic functionality 7 . In the eye, RPE sits on an ECM called Bruch’s membrane which provides structural support and cues affecting e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that cryopreservation decreases the expression of certain adhesion molecules on CD34 + hematopoietic progenitor cells 6 . Human umbilical vein endothelial cells have also been shown to be vulnerable to cryopreservation which can lead to lowered angiogenic functionality 7 . In the eye, RPE sits on an ECM called Bruch’s membrane which provides structural support and cues affecting e.g.…”
Section: Introductionmentioning
confidence: 99%